PengaruhDebt to Equity Ratio, Net Profit Margin dan Return On Equity Terhadap Harga Saham Pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Qahfi Romula Siregar; Rinaldi Rambe; Jumeida Simatupang (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to determine whether there is an effect of Debt to Equity, Net Profi Margin and Return On Equity on Share Prices in Property and Real Estate Companies listed on the Indonesia Stock Exchange. The approach used is an associative approach. The population in this study were property and real estate companies listed on the Indonesia Stock Exchange for the period 2017-2019. Samples were taken using purposive sampling method, in order to obtain 14 companies as samples. And using multiple linear regression analysis methods, classical assumption test, t test (partial test), f test (simultaneous test) and coefficient of determination with the help of software SPSS V.20 (Statistical Product and Service Solutions). Based on the results of the study, it can be concluded that partially Net Profit Margin has a significant effect on stock prices, while the Debt to Equity Ratio, Return On Equity has no and insignificant effect on stock prices. And simultaneously, Debt to Equity, Net Profi Margin and Return On Equity have a significant effect on Share Prices in Property and Real Estate Companies listed on the Indonesia Stock Exchange for the 2017-2019 Period.